2012
DOI: 10.1186/1751-0147-54-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of herd BRSV and BHV-1 seroprevalence with respiratory disease and reproductive performance in adult dairy cattle

Abstract: BackgroundThe aim of this study was to detect the associations between bovine herpesvirus 1 (BHV-1) status of a herd and respiratory disease (BRD) occurrence and reproductive performance in pregnant heifers and cows. The association between management-related factors and higher BRD occurrence was also estimated.MethodsSerum samples, collected from cows and youngstock from 103 dairy cattle herds, were analyzed for antibodies against BHV-1, bovine respiratory syncytial virus (BRSV), bovine viral diarrhoea virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
2
29
1
1
Order By: Relevance
“…In a larger study of Estonian dairy herds comprising 9,637 animals in 65 seropositive and 38 seronegative herds, BoHV-1 was found to be significantly related to reproductive performance with the highest risk of increased insemination index and abortions occurring in herds with a moderate seroprevalence [23]. The odds ratios for these two events were 5.2 (95% C.I.…”
Section: Reviewmentioning
confidence: 99%
“…In a larger study of Estonian dairy herds comprising 9,637 animals in 65 seropositive and 38 seronegative herds, BoHV-1 was found to be significantly related to reproductive performance with the highest risk of increased insemination index and abortions occurring in herds with a moderate seroprevalence [23]. The odds ratios for these two events were 5.2 (95% C.I.…”
Section: Reviewmentioning
confidence: 99%
“…From our previous studies we reported a significant association between high occurrence of respiratory disease in unweaned calves and the presence of BHV-1 among cows (Raaperi et al, 2012b). However, BHV-1 was not significantly associated with high respiratory disease occurrence among heifers (Raaperi et al, 2012b) or cows (Raaperi et al, 2012c). Unfortunately there is no obligation to insert disease incidence data into the EARC database, so we could not test the change of respiratory disease incidence statistically.…”
Section: Discussionmentioning
confidence: 65%
“…In Belgium, the presence of BRSV was detected in 40% of tested beef cattle herds (Pardon et al 2011). In Estonia, the prevalence of BRSV was found to be 49% among dairy herds (Raaperi et al 2012). Similar findings have been reported in countries directly bordering Poland.…”
Section: Discussionmentioning
confidence: 98%